6-Pentyl-α-Pyrone from Trichoderma gamsii Exert Antioxidant and Anti-Inflammatory Properties in Lipopolysaccharide-Stimulated Mouse Macrophages - Jae Sung Lim; Joo-Hyun Hong; Da Young Lee; Xiangying Li; Da Eun Lee; Jeong Uk Choi; Kwang Youl Lee; Ki Hyun Kim; Young-Chang Cho (MDPI AG, 2023)
Filamentous fungi produce several beneficial secondary metabolites, including bioactive compounds, food additives, and biofuels. Trichoderma, which is a teleomorphic Hypocrea that falls under the taxonomic groups Ascomycota and Dikarya, is an extensively studied fungal genus. In an ongoing study that seeks to discover bioactive natural products, we investigated potential bioactive metabolites from the methanolic extract of cultured Trichoderma gamsii. Using liquid chromatography-mass spectrometry (LC-MS), one major compound was isolated and structurally identified as 6-pentyl-α-pyrone (6PP) based on nuclear magnetic resonance data and LC-MS analysis. To determine its antioxidant and anti-inflammatory activity, as well as the underlying mechanisms, we treated lipopolysaccharide (LPS)-stimulated Raw264.7 mouse macrophages with 6PP. We found that 6PP suppresses LPS-induced increase in the levels of nitric oxide, a mediator of oxidative stress and inflammation, and restores LPS-mediated depletion of total glutathione by stabilizing nuclear factor erythroid 2-related factor 2 (Nrf2), an antioxidative factor, and elevating heme oxygenase-1 levels. Furthermore, 6PP inhibited LPS-induced production of proinflammatory cytokines, which are, at least in part, regulated by heme oxygenase-1 (HO-1). 6PP suppressed proinflammatory responses by inhibiting the nuclear localization of nuclear factor kappa B (NF-κB), as well as by dephosphorylating the mitogen-activated protein kinases (MAPKs). These results indicate that 6PP can protect macrophages against oxidative stress and LPS-induced excessive inflammatory responses by activating the Nrf2/HO-1 pathway while inhibiting the proinflammatory, NF-κB, and MAPK pathways.